Geometric Semantic Genetic Programming with Normalized and Standardized Random Programs - Bakurov, Illya (2024)
Bakurov, I., Muñoz Contreras, J. M., Castelli, M., Rodrigues, N., Silva, S., Trujillo, L., & Vanneschi, L. (2024). Geometric Semantic Genetic Programming with Normalized and Standardized Random Programs. Genetic Programming And Evolvable Machines, 25, 1-29. Article 6. https://doi.org/10.1007/s10710-024-09479-1 --- This work was partially supported by FCT, Portugal, through funding of research units MagIC/NOVA IMS (UIDB/04152/2020) and LASIGE (UIDB/00408/2020 and UIDP/00408/2020). This work also was supported by CONACYT (Mexico) Project CF-2023-I-724, TecNM (Mexico) Project 16788.23-P and Project 17756.23-P. José Manuel Muñoz Contreras was supported by CONACYT scholarship 771416; Nuno Rodrigues was supported by FCT PhD Grant 2021/05322/BD.